Fostering the Sense of Belonging: Cultivating Educational Values through a Cultural Association - Sung, Minjeong; Gounko, Tatiana (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2023)
The study delves into the influence of an on-campus, student-led Cultural Association on the experiences of minority students within a predominantly White institution (PWI). This research employed qualitative methods. It primarily utilized in-depth, semi-structured interviews to gather data from five international students attending a comprehensive public research university on the West Coast of Canada. The findings revealed that the Cultural Association significantly contributed to the social and academic integration of the participants within their new institutional and social milieu. By cultivating a sense of belonging, the Association aided the participants in overcoming initial hurdles, such as isolation and acknowledging their status as minorities in the PWI setting. The Association and its members played a crucial role in providing spaces for cultural affirmation, championing diversity, facilitating social inclusion, and nurturing a sense of belonging.